Model procesu innowacyjnego w bankowości - Kotliński, Grzegorz (Model of innovation process in banking, 2006)
Contemporary banks are the financial institutions of public trust which have to take care to maintain this image. Therefore, they should avoid risk related undertakings. On the other hand, however, these are the banks which establish pro - innovation enterprises forefront in Poland. This can be proved by the results of research. It is a proof of creating extremely efficient process of technological innovation diffusion as part of management. In this paper a selected set of theories has been chosen and verified in Polish environment. The purpose of this discussion is making a proposal of a rational and modernized model that explains the tasks and functions of particular elements that build the innovation diffusion process in banking.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 32-40